The Relationship Between Knowledge and Personal Safety Skills As A Efforts to Prevent Sexual Harassment in College Students - Rosa Azizah; Ira Nurmala (Green Publisher Indonesia, 2024)
Sexual harassment ranks first among the cases of sexual violence in educational institutions. The college has become one of the educational institutions with a high case rate. Given that sexual harassment can harm a person as it can have a physical, psychological, and social impact, it is necessary to prevent sexual abuse with personal safety skills consisting of recognize, resist, and report. One of the factors that influences the prevention of sexual harassment is knowledge. The aim of this study is to look at the relationship between knowledge and personal safety skills as behavioral efforts to prevent sexual harassment in students. This research is a quantitative analysis of the type of observational analytics with cross sectional design. Respondents to this study were active students of Airlangga University in the academic year 2023/2024 and a total of 420 respondents were obtained using accidental sampling method. The data collection uses questionnaires and is processed with Spearman's analysis that shows the strength of the relationship. The results show a very strong relationshiip (r=0.824) between knowledge and personal safety skills as an attempt to prevent sexual harassment in students. It is hoped that the campus will maximize its efforts to prevent sexual harassment by increasing the knowledge of students and citizens of the campus about sexual abuse, facilitating training in personal safety or self-care skills, expanding media information and access services for reporting sexual assault, as well as monitoring and periodically evaluating programmes that have been conducted in the campus area.